(untitled) (Swiss Medical Weekly, 2017)
INTRODUCTION To capitalise on the opportunities that the smoking ban legislation in Switzerland offers for the prevention of tobacco-related diseases, a smoking cessation programme in a workplace setting was developed and implemented in companies across the language and cultural regions of Switzerland. Our goal was to identify factors associated with relapse into smoking that may be overcome during training sessions or that should be considered for the optimisation of future interventions. METHODS Between 2006 and 2012, 1287 smokers aged 16 to 68 years voluntarily attended smoking cessation training at their workplace. The intervention was based on a cognitive behavioural group therapy combined with individual proactive telephone counselling. The evaluation consisted of three anonymised questionnaires (pre- and postintervention, and 12-month follow-up). In this prospective cohort study, we investigated the association of smoking quit rates with training and participant characteristics, including withdrawal symptoms, by use of multilevel logistic regression analysis with a random intercept for training courses. RESULTS The self-reported abstinence rate was 72.4% at the end of the training, and 18.6% 1 year later. The risk of relapse during the training was positively associated with the number of years and daily cigarettes smoked, and negatively with increased appetite, sleeping troubles and satisfaction with learned techniques. Failed abstinence within the first year was associated with younger age, higher numbers of daily smoked cigarettes and unsuccessful recent quit attempts. CONCLUSION Our evaluation suggests that younger and more addicted smokers attending smoking cessation trainings may need additional support to achieve long lasting abstinence rates. Offering smoking cessation training in a workplace setting can achieve reasonable long-term quit rates, but a subset of employees needs additional support at the group or personal level. IMPLICATIONS Group behaviour therapy could be an effective method to achieve long-term smoking abstinence. The workplace is an important setting to reach and encourage a large number of smokers to participate in a smoking cessation programme, but only few studies investigated its potential. The findings of this study of a modern real-life workplace-based smoking cessation programme endorse the effectiveness and viability of cognitive behavioural group therapy. This group-level intervention at the workplace may be insufficient for young and heavy smokers, as well as women with increased appetite after cessation, who potentially benefit from re-intervention and additional individual level counselling.